The Interplay of Mental Budgeting, Self-Control, and Financial Behavior: Implications for Individual Financial Well-Being - Ali, Syed Atif; Aslam, Sumaira; Majeed, Muhammad Ussama; Usman, Muhammad (Pakistan Journal of Humanities and Social Sciences, 2024)
According to behavioral finance, people are not always rational in managing their finances. The financial stability of a person is directly linked with the spending style and pattern of the individual. This research investigates how mental budgeting influences financial behaviors and altogether financial stability, with a focus on the moderating effect of self-control. To explore this, we studied 294 people to see how mental budgeting affects their financial management and well-being, and how self-control plays a role in this process. A self-administered questionnaire was adapted to gather responses of the employees working in various organizations in Lahore. Smart PLS and SPSS were utilized to analyze and measure the responses collected from respondents. This study found that people are able to better manage their finances when they use mental budgeting. Similarly, there is clear evidence that mental budgeting has an association with financial well-being and financial behavior. The path coefficient uncovers the moderating impact of self-control on financial management behavior and financial wellness. These findings suggest that teaching people about mental budgeting and self-control in financial education programs might help them make better financial decisions. This study adds to our understanding by showing how these factors work together to influence financial behavior, highlighting the need for more tailored financial advice that considers both mental budgeting and self-control. This research helps clarify how people can better manage their finances through both mental strategies and behavioral control, contributing valuable insights into effective financial management practices.